2017
DOI: 10.1111/wre.12269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling and in sacco digestion on the viability of seeds of selected weed species

Abstract: The germinability and viability of mature seeds of five grass (Hordeum spp., Bromus diandrus, Vulpia spp., Avena fatua and Lolium rigidum) and seven broadleaved weed species (Echium spp., Physalis hederifolia, Solanum elaeagnifolium, Raphanus raphanistrum, Marrubium vulgare and Malva parviflora) that were either untreated, ensiled for a minimum of three months, underwent 48 h in sacco digestion in steers or ensiled prior to digestion were tested for germinability and viability. Ensiling and digestion both redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 21 publications
2
23
2
Order By: Relevance
“…However, regarding the HS species the seed-killing efficacies of our silages were low compared to other long-term studies (Mayer et al, 2000;Koarai et al, 2015;Simard and Lambert-Beaudet, 2016). Instead, the killing efficacy in our experiments was more in the range of studies that ensiled HS seeds for a maximum of 3 months reducing the viability of HS species by about half on average (Woodward, 1940;Mayer et al, 2000;Stanton et al, 2012;Simard and Lambert-Beaudet, 2016;Piltz et al, 2017).…”
Section: Seed-killing Efficacy Of Ensilingcontrasting
confidence: 54%
See 3 more Smart Citations
“…However, regarding the HS species the seed-killing efficacies of our silages were low compared to other long-term studies (Mayer et al, 2000;Koarai et al, 2015;Simard and Lambert-Beaudet, 2016). Instead, the killing efficacy in our experiments was more in the range of studies that ensiled HS seeds for a maximum of 3 months reducing the viability of HS species by about half on average (Woodward, 1940;Mayer et al, 2000;Stanton et al, 2012;Simard and Lambert-Beaudet, 2016;Piltz et al, 2017).…”
Section: Seed-killing Efficacy Of Ensilingcontrasting
confidence: 54%
“…The potential of ensiling to reduce plant seed viability was tested on 10 different dicotyledonous plant species. We did not study monocotyledonous species because other studies have already demonstrated that, with few exceptions, they quickly lose their viability during ensiling (e.g., Blackshaw and Rode, 1991;Lück, 2012;Koarai et al, 2015;Piltz et al, 2017). Our selection should include species that are important weeds, and species that have a high probability of entering silages and represent a wide range of different seed traits.…”
Section: Species Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piltz et al . () found variable results in steers when incubating weed seeds for 48 h. In many of the tested weed species, the rumen caused a reduction in viability but unexpectedly increased viability in a few seeds compared with the control. In sheep, no decrease in germination was found in the hard‐coated species Malva parviflora L. , germination being higher than 90% after 12, 24, 36 or 48 h of rumen storage (Michael et al ., ).…”
Section: Discussionmentioning
confidence: 96%